A Comparative Study of Phenotypic Variability and Physico-Mechanical Properties of Dual-Purpose Flax Fiber Varieties in India. Issue 17 (2nd December 2022) - Pandey, Ritu; Tiwari, Nalini; Dubey, Amarish; Jose, Seiko; Kambo, Neelu; Joshi, Shubham; Chauhan, Vinay Kumar; Basu, Gautam
ABSTRACT: The physico-mechanical characteristics of fibers extracted from seven dual-purpose flax (DPF) and two fiber flax (FF) varieties grown in India were investigated to determine their suitability for various textile and technical applications. The selected varieties were evaluated in terms of the plant's phenotypic traits, maturity, fiber, and seed production. The flax fibers, after water retting, were examined for extent of retting, fiber mass loss, quantity, length, fineness, color, tenacity, and elongation. Fibers were characterized by thermogravimetric analysis (TGA), scanning electron microscopy (SEM), Fourier Transform Infrared spectroscopy (FTIR), and X-ray diffractometry (×RD). Despite significant differences in phenotypic attributes among the nine varieties, except fiber tenacity, the difference in fineness, length, and elongation was found to be negligible. Thermo-chemical properties of the fibers also showed similarity across the nine varieties.